Transition from US GAAP to IFRS: Analysis of Impact on Income Tax Administration in USA - Jana Roe (European Financial and Accounting Journal, 2014)
When SEC and FASB started considering replacing US GAAP with IFRS, the impact of this change had to be considered by the various stakeholders in the financial reporting process in the U.S., including the various preparers and users of financial statements, including the Tax Administration, IRS. Since 2009, taxpayers in the U.S. are allowed to use IFRS as a starting point for reconciliation of book results to taxable income or loss, an option utilized by approximately 200 companies in that year. In 2010, TIGTA issued a report describing the state of preparedness for the potential transition from US GAAP to IFRS, outlining activities such as education of field agents, technical analysis of the potential impact of changes to financial reporting standards, consultation of current issues related to IFRS with taxpayers and preparers. Specific technical tax issues related to transition from US GAAP to IFRS include LIFO, leasing, component depreciation, and uncertain tax positions; non-technical tax issues related to IFRS adoption include taxpayer and agent education, regulatory adjustments, developing new audit strategies. In addition to federal tax considerations, state tax authorities and taxpayers are preparing for the impact of IFRS adoption on state and local tax administration, impacting issues such as sales, property, and payroll apportionment and equity-based taxes. The main research questions relate to empirical research related to the micro and macro economic impact of the transition from US GAAP to IFRS.
Keywords: H25; M41; 650; Tax administration; IFRS; US GAAP; IRS; TIGTA; LIFO; Financial reporting standards